ГОСУДАРСТВЕННОЕ РЕГУЛИРОВАНИЕ И УПРАВЛЕНИЕ ЛЕСТНЫМ ХОЗЯЙСТВОМ (Journal of actual problems of jurisprudence, 2019)
In given article the author reveals the history of a state administration and regulation of forest fund of Republic of Kazakhstan .As by the author on the basis of the analysis of actions of the legislation and state administration system forest fund it is given somerecommendations about perfection of the forest legislation.